From theology to mystagogy. The interiorisation of the Protestant tradition by a world citizen: Dag Hammarskjöld - J. Huls (Acta Theologica)
This essay presents as paradigm the reflection of Dag Hammarskjöld on the history of his belief. It investigates how his initial expression of theological concepts gradually became a mystagogical process, interiorising the religious traditions in which he has grown up.